Environmental Effects on Allergen Levels in Commercially Grown Non-Genetically Modified Soybeans: Assessing Variation Across North America - Stevenson, Severin E.; Woods, Carlotta A.; Hong, Bonnie; kong, Xiaoxiao; Thelen, Jay J.; Ladics, Gregory S. (Frontiers in Plant Science, 2012)
Soybean (Glycine max) is a hugely valuable soft commodity that generates tens of billions of dollars annually. This value is due in part to the balanced composition of the seed which is roughly 1:2:2 oil, starch and protein by weight. In turn, the seeds have many uses with various derivatives appearing broadly in processed food products. As is true with many edible seeds, soybeans contain proteins that are anti-nutritional factors and allergens. Soybean, along with milk, eggs, fish, crustacean shellfish, tree nuts, peanuts and wheat, elicit a majority of food allergy reactions in the United States. Soybean seed composition can be affected by breeding, environmental conditions (e.g. temperature, moisture, insect/pathogen load, and/or soil nutrient levels). The objective of this study was to evaluate the influence of genotype and environment on allergen and anti-nutritional proteins in soybean. To address genetic and environmental effects, four varieties of non-GM soybeans were grown in six geographically distinct regions of North America (Georgia, Iowa, Kansas, Nebraska, Ontario, and Pennsylvania). Absolute quantification of proteins by mass spectrometry can be achieved with a technique called multiple reaction monitoring (MRM), during which signals from an endogenous protein are compared to those from a synthetic heavy-labeled internal standard. Using MRM, eight allergens were absolutely quantified for each variety in each environment. Statistical analyses show that for most allergens, the effects of environment far outweigh the differences between varieties brought about by breeding.